2020
DOI: 10.1167/iovs.61.11.43
|View full text |Cite
|
Sign up to set email alerts
|

Jmjd3 Plays Pivotal Roles in the Proper Development of Early-Born Retinal Lineages: Amacrine, Horizontal, and Retinal Ganglion Cells

Abstract: Trimethylation of histone H3 at lysine 27 (H3K27me3) is a critical mediator of transcriptional gene repression, and Jmjd3 and Utx are the demethylases specific to H3K27me3. Using an in vitro retinal explant culture system, we previously revealed the role of Jmjd3 in the development of rod bipolar cells; however, the roles of Jmjd3 in the development of early-born retinal cells are unknown due to limitations concerning the use of retinal explant culture systems. In this study, we investigated the roles of Jmjd3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Histone modifiers, such as the demethylases JMJD3, UTX, and LSD1, provide additional regulation. For example, the loss of JMJD3 and UTX affects the proper development of inner retinal cells such as bipolar, amacrine, and horizontal cells (Iida et al, 2014;Iwagawa et al, 2020;Umutoni et al, 2020). Lsd1 inhibition directly impacts the survival of specific retinal cells, such as RGCs and photoreceptors (Tsutsumi et al, 2016;Popova et al, 2021), and alters regulation of microRNAs, such as the miR-21-5p/NLRP12 axis, to facilitate RGC pyroptosis (Yu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Histone modifiers, such as the demethylases JMJD3, UTX, and LSD1, provide additional regulation. For example, the loss of JMJD3 and UTX affects the proper development of inner retinal cells such as bipolar, amacrine, and horizontal cells (Iida et al, 2014;Iwagawa et al, 2020;Umutoni et al, 2020). Lsd1 inhibition directly impacts the survival of specific retinal cells, such as RGCs and photoreceptors (Tsutsumi et al, 2016;Popova et al, 2021), and alters regulation of microRNAs, such as the miR-21-5p/NLRP12 axis, to facilitate RGC pyroptosis (Yu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As the chromatin in mouse rods is already hypercondensed, the upregulation of repressive methylation marks such as H3K27me3 push nuclei towards pyknosis and subsequent cell death [ 45 ], while the same disease mechanism may not happen in mouse cones due to their different natural chromatin condensation. The role of H3K27me3 and their corresponding demethylases is complex, with studies showing the role of Kdm6b (a demethylase of H3K27me3) in the development of the earlier born retinal cells; amacrine, horizontal, retinal ganglion cells as well as rod bipolar cells [ 46 ]. Raeisossadati et al 2019 also showed that injection of GSK-J1 in PN (Postnatal day) 0 mice identified an integral role for Kdm6b in processes such as cell proliferation, apoptosis, differentiation, senescence and cellular reprogramming [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trimethylation of histone H3 at lysine 27 (H3K27me3) is a mediator of transcriptional gene repression, and the Jumonji family (Jmj family) member jumonji domain-containing protein D3 (JMJD3) is a demethylase specific to H3K27me3. 13 The H3K27me3 demethylase JMJD3 is implicated in neurological lesion-induced chronic pain. 14 In contrast, the Trpv1 promoter is regulated by H3K27me3.…”
Section: Glossarymentioning
confidence: 99%